Sailing context in PISA-like mathematics problems - Efriani, Arvin; Putri, Ratu Ilma Indra; Hapizah (Journal on Mathematics Education, 2019)
Developing PISA like mathematics problems using daily life context helps to improve the quality of learning. This study aimed to generate a valid, practical, and having potential effects on mathematics literacy ability PISA like mathematics problems with the context of sailing in the 2018 Asian Games. This research involved three expert reviews and 32 fifteen-years-old tenth-grade students of SMA N 10 Palembang, a public senior high school in Palembang Indonesia, as the research subjects. This study used the design research method of development studies type. The data were collected through documentation, walkthrough, tests, and interviews. The problem developed in this study is related to the length of wood required to span the sail. The results show that the problems are valid. The validity was viewed from its compatibility with the PISA framework, in which it had related the problems with daily life context of sailing in the 2018 Asian Games and space and shape content. The problems are also practical, viewed from students' understanding of the problem. And, the problems have potential effects when tested in learning issue of mathematical literacy ability. The dominant ability is reasoning and representation ability, while the communication ability is still low because the students do not give detailed answers.